Distributed Acoustic Sensing Applied to 4D Seismic: Preliminary Results From the CO2CRC Otway Site Field Trials. - Correa, J.; Freifeld, B.; Robertson, M.; Pevzner, Roman; Bona, Andrej; Popik, Dmitry; Yavuz, Sinem; Tertyshnikov, K.; zIRAMOV, S.; Shulakova, V.; Daley, T. (2017)
Carbon geosequestration requires the mapping and monitoring of the injected CO2 to assure the gas is safely stored in the formation. In this context, Distributed Acoustic Sensing (DAS) has the potential to reduce the costs of seismic operations and increase equipment survivability. Field demonstrations show that DAS can be used for reservoir monitoring in geosequestration applications but most of its studies are limited to borehole seismic surveys, while very little has been published towards DAS for surface seismic. To bridge this gap, capability for seismic monitoring using a 3D DAS array was tested during a test CO2 injection of the CO2CRC Otway Project (Victoria, Australia). DAS was deployed together with geophones along eleven receiver lines and data were acquired before and after the injection of 5kt, 10kt and 15kt of supercritical CO2. Processing of DAS data is very challenging due to strong angle dependence of its sensitivity and very large volumes of recorded data. Preliminary processing results show that we can identify the main reflectors but noise is still strong. The results also show strong azimuth dependence of DAS sensitivity.